Broadband Silver Ribbon-Embedded Graphene and h-BN Optical Modulator With High Modulation Depth and Extinction Ratio and Low Switching Voltage - Hossein Karimkhani; Hamid Vahed (IEEE Photonics Journal, 2024)
Herein, we theoretically demonstrate a broadband hybrid plasmonic electro-absorption optical modulator with integrated silver nanoribbons. We have examined two structures. The first one includes two layers of graphene and two layers of hexagonal boron nitride (h-BN). Silver nanoribbons are placed on the Molybdenum Disulfide ( $MoS_2$ ) layer. In the second structure, we covered the nanoribbon arrays with extra graphene, $MoS_2$ , and h-BN layers. The effect of the gap between the silver nanoribbons is analyzed for the effective refractive index, modulation depth (MD), Extinction Ratio (ER), Figure of Merit (FoM), and loss. The best results illustrate that the highest amount of the effective refractive index is 5.65, and the highest amount of the loss is 2.2 dB/μm in the chemical potential of 0.65 eV at the wavelength of 1.3 μm. The maximum MD and FoM are 28.37 dB/μm and 62.93 at 1.3 μm, respectively. The calculations show that this electro-absorption modulator has a modulation bandwidth of 411.25 GHz and 27.18 fJ/bit energy consumption. This modulator achieves a high MD, ER, and FoM with a small footprint and low switching voltage. The study demonstrates that the modulator can achieve a high level of modulation depth with low energy consumption and loss.